The Relationship Between Socio-Cultural and Self-Care for Mental Health Generation Z: A Cross-Sectional Study on Mataraman Ethnicity, East Java, Indonesia - ALFIANTO, AHMAD GUNTUR; Sukmawati, Ika; Sulaksono, Ari Dwi (Jurnal Keperawatan Malang, 2023)
Background: Negative coping for generation Z causes psychosocial problems. One of these problems is the lack of mental health self-care and one of the deficiencies of these factors is socio-cultural problems. The Mataraman ethnic group is the largest ethnic group in East Java. With the largest population of Generation Z, this ethnicity is always guided by the culture and values ??of that ethnicity. Objective: to analyze socio-cultural relations with mental health self-care for the Mataraman ethnic group. Method: the research design used is an analytical survey and a cross sectional approach. The sample technique used was purposive sampling with a total sample of 420 generation Z of Mataraman ethnicity. Data was collected by distributing questionnaires with Googleform and the media used were WhatsApp, Facebook, Twitter, Tiktok and Instragram groups. The test used is the person correlation test. The instruments used were the Cultural Connected Scale-California (CCS-CA) for socio-cultural variables and the Mindful Self Care Scale (MSCS) for mental health self-care variables. Results: The most common socio-cultural variable for generation Z of Mataraman ethnicity was tradition (Mean ± SD; 49.89 ± 6.87), while in the mental health self-care variable the largest average was physical care (Mean ± SD; 21.89 ± 4 .63), and the value of the relationship between the two variables is a p value of 0.000 while the person test value is 0.29. Conclusion: there is a relationship between socio-culture and mental health self-care in generation Z of Mataraman ethnicity, but these two variables have a weak relationship. So that suggestions for subsequent research can be analyzed related to other factors such as perceptions and beliefs. As well as carrying out mental health nursing interventions with cultural sensitivity.